(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To develop diagnostic criteria for common traditional medicine syndromes and to systematize and describe the characteristics of herbal formulas and medicinal plants used as adjunctive treatments for atopic dermatitis based on the literature. Methods: A descriptive literature review was conducted based on traditional medicine documents concerning atopic dermatitis. Literature selected according to predefined criteria. The frequencies of traditional medicine syndromes, clinical manifestations, herbal formulas, and medicinal herbs related to atopic dermatitis were extracted and calculated using Microsoft Excel for statistical analysis. Results: From 60 traditional medicine documents, 7 syndromes were identified, of which 3 were included in the development of diagnostic criteria: Dampness-Heat (12 symptoms), Wind-Heat (7 symptoms), and Wind-Blood-Dryness (10 symptoms). A total of 249 formulas used as adjunctive treatments for atopic dermatitis were recorded, with 7 formulas used most frequently; these were mainly administered orally in decoction form. Among 274 medicinal materials, 197 were herbal drugs, most of which were cold in nature and bitter or sweet in taste, predominantly entering the Liver and Spleen meridians. The most commonly used plant parts were roots, leaves, fruits, and rhizomes. These materials belonged to 38 botanical orders, with Lamiales and Asterales being predominant. Conclusion: This study provides preliminary evidence for the standardization of traditional medicine syndrome-based diagnosis in atopic dermatitis and for the systematization of literature-derived data on herbal adjunctive therapies, thereby laying a foundation for future research and clinical application.